Modifying an Equation to Predict the Asphaltene Deposition in the Buzurgan Oil Field - Hasan, Raad Mohammed; A. Al-haleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
Buzurgan oil field suffers from the phenomenon of asphaltene precipitation. The serious negatives of this phenomenon are the decrease in production caused by clogging of the pores and decrease in permeability and wettability of the reservoir rocks, in addition to the blockages that occur in the pipeline transporting crude oil. The presence of laboratories in the Iraqi oil companies helped to conduct the necessary experiments, such as gas chromatography (GC) test to identify the components of crude oil and the percentages of each component, These laboratory results consider the main elements in deriving a new equation called modified colloidal instability index (MCII) equation based on a well-known global equation called colloidal instability index (CII) equation. The modified (MCII) equation is considered an equation compared to the original (CII) equation because both equations mainly depend on the components of the crude oil, but the difference between them lies in the fact that the original equation depends on the crude oil components at the surface conditions, while the new equation relies on the analysis of crude oil to its basic components at reservoir conditions by using (GC) analysis device. The components of the crude oil in the reservoir conditions according to the number of carbon atoms of each component compared with the elements of the original equation, which are (saturates, aromatics, resins, and asphaltene). The new MCII equation helps in predicting the possibility of asphaltene precipitation which can be used and generalized to other Iraqi oilfields as it has proven its worth and acceptability in this study.